INFEKSI CANDIDA ALBICANS PADA NECROTIZING FASCIITIS: LAPORAN KASUS - Prestya, Pebrian Diki; Putri, Farah Asnely; Arumsari, Asri (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2024)
Introduction: Necrotizing fasciitis is an infection with very rapid progress affected subcutaneous tissue, spread to the fascia lead to subcutaneous blood vessels thrombosis. Hence, caused necrosis of skin. Frequently polymicrobial, caused by β-haemolytic bacteria such as Streptococcus, Staphylococcus spp. and obligate anaerobes. Necrotizing fasciitis due to fungal infection is a rare case, only five cases were recently reported where Candida albicans was identified as necrotizing fasciitis microorganism Case Report: A 51 years old male patient was referred to Emergency Room at Hasan Sadikin General Hospital, Bandung complaints of swelling accompanied by pain in the left cheek extended to eye and neck, with clinical features shown necrosis of the skin, fluctuations and crepitations. The patient was diagnosed as necrotizing fasciitis. The patient has a history of systemic disease which is diabetes mellitus type 2 with hyponatremia and chronic kidney disease. The patient performed necrotomy debridement and incision drainage at submental, temporal and bukal region in general anaesthesia, then followed by wound care with modern dressings. Bacteria culture shown the growth of C.albicans Conclusion: Necrotizing fasciitis caused by C. albicans is a rare case. Several factors that can increase Candida virulence lead to invasive soft tissue infections, the importance was anti-fungal therapy in necrotizing fasciitis beside broad-spectrum antibiotic therapy of this case. Additionally, postoperative wound care was necessary for encourage wound healing